Public archaeology and prehistory in Sicily - Giannitrapani, Enrico
We have invited an active prehistorian from Sicily to set two important events in context: the first conference on Sicilian prehistory held at Corleone and the important exhibition held in Palermo over the last year. Sicily is one of the richest regions of the world for archaeological remains and yet has not received the attention it deserves. This is especially true for prehistory, which has suffered from devaluation by ancient historians such as Moses Finley (1979: 13)Ð'the Greek settlers found wives among the natives, and also a labour force. Other than that, however, the lasting effects of the pre-Greek populations would not seem to have been very significant'Ðand where it has often been assumed that everything of worth came from outside. Enrico Giannitrapani presents the emerging consciousness of Sicilians that their island was not founded by the Greeks.